Measuring Passenger Car Unit (PCU) at Four Legged Roundabout using Time Occupancy Data Collected from Drone - Sugiarto Sugiarto; Fadhlullah Apriandy; Ruhdi Faisal; Sofyan M. Saleh (Aceh International Journal of Science and Technology, 2018)
This study aims to measure the values of passenger car unit (PCU) at a four-legged roundabout based on the time occupancy data in complex traffic operation. Within mixed traffic, the PCUs are needed as a equivalency factor to convert various type of vehicles to a standard unit. The unit of PCU was used to determine capacity and level of service of specific the traffic condition. The composition of vehicles going through the intersection,  mostly varies and each type of vehicles tends to have diverse effects on capacity and level of services. Consequently, a conversion factor from various vehicles to a standard vehicle is required.   The data of this study was collected using a drone at the investigated roundabout at one of the major roundabouts in Aceh Besar, Aceh province, Indonesia. The method used was the vehicle's time occupancy, in which  calculated from  the average time required by each vehicle to pass through the roundabout area. The results show that the PCU values obtained is 0.16 for motorcycle, 0.59 for rickshaw, 1.07 for pickup, 1.91 for a medium vehicle, and 3.76 for the heavy vehicle. These results should be utilized for converting various type of vehicles into PCUs to estimate capacity and level of services, especially at the roundabout trafict. This results may be suitable to revise the Indonesian Traffic Code, named Indonesian Highway Capacity Manual 1997, and useful for ongoing national-level efforts to upgrade the  Indonesian Highway Capacity Manual.